The specific impact of different types of exercise on the physical performance of older preschoolers, taking into account gender and age differences - Dvorkina, N.I.; O.S. , Trofimova; Marinovich, M.A.; Manakova, Ya.A. (Theory and Practice of Physical Culture, 2025)
Objective of the study is to identify the annual dynamics of the impact of various types of exercise on the gender and age indicators of physical working capacity in older preschool children. Methods and structure of the study. The second stage of the study involved preschoolers aged 5 to 6 (boys n = 28 and girls n = 28) and aged 6 to 7 (boys n = 28 and girls n = 28) attending Krasnodar Kindergarten No. 103. The physical education process included exercises of various types of physical culture and health technologies, in which three variants of confidence intervals (moderate, average, high) of model indicators PWC150 were identified when performing stretching, aerobics, fitball-aerobics and exercises on training equipment. Results and conclusions. Three levels of model indicators of physical working capacity PWC150 (moderate, average and high) for various types of exercise (stretching, aerobics, fitball-aerobics and exercise equipment) for older preschoolers have been identified. It has been established that in the practice of physical education for older preschoolers, the most optimal level of the PWC150 indicator is when performing stretching, aerobics, fitball-aerobics, and exercises on training equipment.